Analisis Perilaku Biaya dalam Mendukung Pengambilan Keputusan Manajemen - Lilis Tampubolon; Marta Lafau; Nicolas Hasibuan; Monang Siallagan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze cost behavior in supporting managerial decision-making within companies. Cost behavior refers to changes in costs resulting from changes in the level of business activity and consists of fixed costs, variable costs, and semi-variable costs. Understanding cost behavior is essential because cost information serves as the basis for planning, controlling, evaluating, and making managerial decisions. This research employs a qualitative method with a literature study approach by collecting data from scientific journals, undergraduate theses, final projects, books, and scholarly articles relevant to the research topic. Data analysis was conducted using a descriptive qualitative technique by identifying, classifying, comparing, and interpreting various reference sources related to cost behavior and managerial decision-making. The results indicate that cost behavior plays an important role in supporting managerial decision-making, particularly in profit planning, cost control, pricing decisions, and Cost-Volume-Profit (CVP) analysis. Furthermore, an understanding of cost behavior helps companies improve the effectiveness and efficiency of resource utilization, enabling them to achieve operational objectives optimally. Therefore, cost behavior analysis is an important tool in supporting the success of managerial activities within a company.